Penerapan Terapi Okupasi Menanam Untuk Menurunkan Tingkat Halusinasi Pada Pasien Skizofrenia di RSJD Dr. RM. Soedjarwadi Klaten - Agustina Kartika Sari; Wahyu Reknoningsih; Sitti Rahma Soleman (Jurnal Ventilator, 2023)
Background: Skizofrenia is a mental disorder where the prevalence is actually small, affecting about 1% of the world's population. In Central Java alone, there are 8.7% of the population who have schizophrenia, this is one of the fifth highest number of professions. Planting occupational therapy aims to minimize the patient's interaction with his unreal world, bring out thoughts, feelings, or emotions that have influenced unconscious behavior, provide joy, entertainment, and distract the patient from the hallucinations he is experiencing so that the patient's mind is not focused on his special hallucinations. in patients with auditory hallucinations (Yuniar N.S et al., 2019). Objective: To find out the results of the implementation of the application of occupancy therapy to control the level of hallucinations. Method: The method used in this application is descriptive with a case study research design totaling 2 respondents, the research instrument is the AHRS questionnaire observation sheet. Findings Before being given occupational therapy, Mrs. G was planted in the category of moderate hallucinations and Mrs. M was in the category of severe hallucinations. After being given occupational therapy, planting for 6 times, Mrs. G was in the category of mild hallucinations and Mrs. M was in the category of moderate hallucinations. Implication: Planting Occupational Therapy has an effect on controlling the level of hallucinations in patients with auditory hallucinations.